Psychometric characteristics of the Peruvian adaptation of the Pediatric Symptom Checklist (PSC-17) - Tirado-Hurtado, Benilde (2024)
The COVID-19 pandemic has greatly affected the mental health of children and adolescents. In Peru, due to containment measures, children and adolescents were subjected to two years of virtual education, further affecting their socioemotional development. The use of the 17-item Pediatric Symptom Checklist (PSC-17) allows early detection of mental health problems in children and adolescents. Objective: To determine the psychometric characteristics of the Peruvian adaptation of the Pediatric Symptom Checklist-17 (PSC-17). Methods: Data were collected from 561 Peruvian schoolchildren (53.3% female; average age=12.23, SD=2.65) who completed the PSC-17 through telephone or video calls made between November 2021 and January 2022. Results: The PSC-17 internal consistency analysis showed a McDonald omega coefficient of 0.7098, indicating acceptable reliability of the instrument. Within the structural analysis, the confirmatory factor analysis (CFA) showed acceptable fit indicators: CFI (0,959), TLI (0,952), RMSEA (0,037), and SRMR (0,048). Conclusion: The Peruvian adaptation of the PSC-17 presents psychometric properties of internal consistency and validity adequate for the measurement of mental health problems in Peruvian children and adolescents, presenting better indicators if some questions are adjusted according to age.